2013
DOI: 10.1002/acr.21861
|View full text |Cite
|
Sign up to set email alerts
|

Diastolic Dysfunction in Rheumatoid Arthritis: A Meta‐Analysis and Systematic Review

Abstract: Objective. To determine if the prevalence of diastolic dysfunction is increased in rheumatoid arthritis (RA) patients. Methods. We conducted a time-and language-restricted literature search to identify studies conducted to compare echocardiographic parameters in patients with RA and controls. The mean difference for echocardiographic variables of interest was calculated using a random-effects model. A systematic review of the literature was performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
3
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 59 publications
(56 reference statements)
4
72
3
10
Order By: Relevance
“…In both studies, RA patients were compared with healthy subjects, and none of the patients or control subjects had any associated comorbidities to verify the effect of the disease on the heart. Three successive systematic reviews with meta-analyses corroborated the above-described findings (4)(5)(6). The first meta-analysis used pooled data from 10 controlled studies and confirmed valvular and pericardial involvement in RA (4), the second confirmed the increased prevalence of left ventricular diastolic dysfunction in patients with RA (5), and the third highlighted the detrimental effect of RA on left ventricular mass (6).…”
supporting
confidence: 53%
“…In both studies, RA patients were compared with healthy subjects, and none of the patients or control subjects had any associated comorbidities to verify the effect of the disease on the heart. Three successive systematic reviews with meta-analyses corroborated the above-described findings (4)(5)(6). The first meta-analysis used pooled data from 10 controlled studies and confirmed valvular and pericardial involvement in RA (4), the second confirmed the increased prevalence of left ventricular diastolic dysfunction in patients with RA (5), and the third highlighted the detrimental effect of RA on left ventricular mass (6).…”
supporting
confidence: 53%
“…In our studies, although the higher LVMI noted in the RA patients with high-ACPA levels fell within the normal range, a progressive increase in LVM is a heart failure precursor in the general population, and strong sudden cardiac death predictor, even in subsets with normal ejection fraction [13,14]. A recent meta-analysis of cross-sectional studies in RA patients without clinical heart failure revealed no consensus on LVMI differences between RA and controls, as higher LVMIs, lower LVMIs and no difference in LVMI have all been reported [10,15]. This could be due to variability in time of assessment along the continuum of the RA disease process.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, diastolic dysfunction has been studied in some other rheumatic diseases such as rheumatoid arthritis, scleroderma, ankylosing spondylitis, and Behçet's disease. [14][15][16][17][18] These studies focused on inflammatory mechanisms, vasculitic and fibrotic changes of the heart which are the causes of distensibility, abnormal diastolic filling, impaired relaxation, and diastolic stiffness of the left ventricle. However, FM is a non-inflammatory disorder different from the aforementioned rheumatic diseases.…”
Section: Discussionmentioning
confidence: 99%